Changes in particulate matter concentrations at different altitudinal levels with environmental dynamics - Zona, Z.; Ali, Z.; Sidra, S.; Nimra, A.; Ahmad, M.; Aziz, K.; Zainab, I.; Quratulain; Ansari, B.; Raza, S. T.; Nasir, Zaheer A.; Colbeck, Ian (Pakistan Agricultural Scientists Forum, 2015)
Ambient air quality is defined not only by the source strength but a variety of meteorological parameters as well. In the current study, ambient concentrations of PM along with temperature and relative humidity levels were monitored at seven different locations of Pakistan. A DustTrak DRX (Model 8533, TSI Inc.) was employed for twenty four hours real time monitoring of particulate matter at the selected sites. A considerable variation was observed in the 24 hour trend of particulate matter (PM) at different locations owing to variation in meteorological conditions due to different altitudes and seasons, and natural and anthropogenic sources in the vicinity. The highest average concentrations of PM2.5 (407 mu g/m(3)) were observed at highest elevation (Makra Peak, Shogran, 3089 m) while lowest averages (102 mu g/m(3)) were obtained at the seaside (Hawks Bay, Karachi, 0 m). On the other hand PMTotal fraction exhibited highest levels at site B (506 mu g/m(3)) and lowest at Site A (121 mu g/m(3)). Correlation factors were determined for PM and meteorological parameters at each location. More research needs to be conducted to have a comprehensive knowledge about the physical parameters controlling particulate dispersal at different altitudes within the country.
Keywords: Particulate matter; Different altitudes; Pakistan; meteorological factors; carbon dioxide